Comparative Study of Biochemical Composition and Nutrient Profile of Four Species of Penaeid Shrimps - Jawahar, Laly Sundarambal; Sankar T. V. (Fishery Technology, 2023)
The biochemical composition and nutrient profile of flower tail shrimp (Metapenaeus dobsoni), brown shrimp (Metapenaeus monoceros), jinga shrimp (Metapenaeus affinis) and kiddi shrimp (Parapenaeopsis stylifera) were evaluated. Significantly higher (p